Poverty Development Post Fiscal Decentralization Policy In Otsus Fund Receiving Province In Indonesia (Case Study: Province Of Papua, West Papua, And Aceh) - Lailan Safina Hasibuan; Prawidya Hariani; Ade Shandra Pratiwi (CERED Indonesia Institute, 2021)
Phenomenon poverty that occurs in the provinces receiving special autonomy funds (Papua, West Papua, and Aceh), where these three provinces are provinces with very high poverty rates. With the implementation of the special autonomy policy and the granting of additional special autonomy funds, these three provinces have not been able to free themselves from the poverty that plagues them. The main purpose of this study is to estimate and prove how the variables of TKD, DOK, and DD affect the Poverty Level. The data used in this study is panel data, where the data collected is cross section data, namely the three provinces that receive special autonomy funds in Indonesia (Papua, West Papua, and Aceh) while the time series data used in this study are collected as many as 4 years, starting from 2017 to 2020. Based on the estimation results using the multiple regression method using E-Views 10 software, goodness of fit (R2) was measured in the first model, a value of 0.5011811 or 50.18% was obtained. Partially, the independent variable is TKD has a negative and insignificant effect and DD has a negative and significant effect on the Poverty Level, while DOK has a positive and significant effect.